Means-oriented or goal-oriented architecture education? (EAAE Annual Conference Proceedings, 2023)
In a fading material culture, where societies have become far from making and only content with image approximations, architectural education, no exception, is suffering from the absence of visual, haptic, and tacit knowledge. When pairing the knowledge of materials with its related issues of resource depletion, climate change, and waste, a new seed for teaching architecture is ready to be planted.